Datos de LC-MS/MS de dos metacestodes de Echinococcus granulosus extraidos de Felis catus - Maglioco, Andrea Florencia (2025)
This work presents, for the first time, the comparative analysis of the LC-MS/MS based molecular profile of two Echimnococcus granulosus metacestodes isolated from two naturally infected unrelated Felis catus. Protein abundance index (emPAI ) analysis showed distitnct proteomic signatures related to parasite metabolism and vitality.